2014
DOI: 10.21608/jappmu.2014.70914
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production and Feed Utilization of Zaraibi Goats Fed Some Forage Protein Sources Such as Berseem or Kochia Silage and Their Mixture With Fodder Beet.

Abstract: Eighteen dairy Zaraibi goats in 2 nd , 3 rd and 4 th season of lactation with average body weight of 37.87kg were divided randomly into three equal groups, to study the effect of substitution of berseem silage by Kochia as a source of protein in silage rations on milk yield, blood profile and feed efficiency of dairy goats. Half the crude protein (CP) requirements of lactating goats were covered from CFM. The other 50% of CP was covered from: berseem silage in the first group (G1), 50% berseem+50% fodder beet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 6 publications
6
2
0
Order By: Relevance
“…Concerning Ca and P contents in blood, despite diminishing differences among treatments, Ca content with G3 ration was lesser significantly than that of G1 and G2 ones, while P content was higher significantly with both tested rations than control one. The obtained values are within the normal physiological ranges that reported by Kaneko (1989) for healthy goats and in the line with the findings of Ahmed et al (2001) and Maged et al (2014) who used mixture of silages such as Kochia-Teosinet and Kochia-fodder beet in rations of dairy goats. The present results are in harmony with those obtained by Fahmy and Fayed (2000) who found insignificant differences respecting contents of total protein, albumen and globulin in blood of sheep and goats fed Kochia indica hay vs. berseem hay in addition concentrate feed mixture to cover 50 % of their energy requirements.…”
Section: Blood Parameterssupporting
confidence: 92%
See 4 more Smart Citations
“…Concerning Ca and P contents in blood, despite diminishing differences among treatments, Ca content with G3 ration was lesser significantly than that of G1 and G2 ones, while P content was higher significantly with both tested rations than control one. The obtained values are within the normal physiological ranges that reported by Kaneko (1989) for healthy goats and in the line with the findings of Ahmed et al (2001) and Maged et al (2014) who used mixture of silages such as Kochia-Teosinet and Kochia-fodder beet in rations of dairy goats. The present results are in harmony with those obtained by Fahmy and Fayed (2000) who found insignificant differences respecting contents of total protein, albumen and globulin in blood of sheep and goats fed Kochia indica hay vs. berseem hay in addition concentrate feed mixture to cover 50 % of their energy requirements.…”
Section: Blood Parameterssupporting
confidence: 92%
“…The daily total DM intake as g/h or g/kgw 0.75 tended to slightly decrease with tested rations (G2 and G3) compared with control group G1, being 683 and 676 vs. 705 g/h and 61.87 and 61.51 vs. 62.22 g/kgw 0.75 , respectively. Similar results were reported by Maged et al (2014) with dairy goats. They found that the highest values of daily feed intake as g/h or g/kgw0.75 were recorded with berseem silage (1141 or 75.31, respectively) then berseemfodder beet silage (1120 or 73.01) and lastly, Kochia-fodder beet silage (1099 or 71.78) respectively.…”
Section: Daily Feed Intake and Water Consumptionsupporting
confidence: 91%
See 3 more Smart Citations